Pediatric Intensive Care Unit: reflection in the light of Florence Nightingale's Environmental Theory - Soraya Bactuli Cardoso; Isabel Cristina dos Santos Oliveira; Tania Vignuda de Souza; Sandra Alves do Carmo (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To reflect on the environment of the Pediatric Intensive Care Unit in the light of the Florence Nightingale's Environmental Theory. Methods: A theoretical-reflexive essay of constructs originated from the final work of a discipline related to the Florence Nightingale's Environmental Theory and the current legislation regarding the environment of the unit. Results: The elements "lighting," "noise," "colors, and varieties of objects," "location of nursing units," and "odors" follow Florence Nightingale's assumptions while the elements "ventilation," "spacing between beds," "furniture" underwent adaptations to suit the current structure of the unit. Final considerations: The environmental theory is a milestone in the history of nursing. Despite the transformations, such as the emergence of intensive care units and the permanence of the family in these units, the nursing team must maintain Florence Nightingale's concern about the environment influencing the health/disease process and promoting an adequate environment for the care of the child and his family.